Impact of the Pandemic: Students Lose Respect for Teachers - Rustim, Salwa Syazwani; Wei Nie, Winnie Tiong; Ejaipi, Abby Earlynnda; Mohd Khairil Azma Panjabi, Nur Izazi Adilah; Zufayri Hussin, Muhammad Shakir; Ismail, Umairah; Husaini, Sarah Najwa; Husin, Mohd Razimi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Pandemik Covid-19 membawa perubahan dalam dunia pendidikan. Murid-murid yang bervariasi latar belakang kehidupan ikut merasai perubahan proses pengajaran dan pembelajaran (PdP) yang membawa kesan kepada tingkah laku murid sama ada yang positif mahupun negatif. Pelbagai masalah dan cabaran yang dihadapi oleh banyak pihak terutama guru dalam membentuk nilai murni dalam kalangan remaja khususnya insan yang bergelar murid. Susulan daripada pandemik ini, perspektif murid dan tingkah laku mereka terhadap guru turut berkurang akibat daripada kesan norma baharu. Kajian ini mengkaji kesan daripada pandemik terutamanya murid hilang rasa hormat terhadap guru. Impact of the Pandemic: Students Lose Respect for Teachers Abstract: The Covid-19 pandemic brought changes in the world of education. Pupils with varied backgrounds experience changes in the teaching and learning process (PdP) which has an impact on pupils' behavior whether positive or negative. Various problems and challenges faced by many parties, especially teachers, in forming good values among teenagers, especially people who hold the title of student. Following this pandemic, students' perspectives and their behavior towards teachers also decreased as a result of the impact of the new norms. This study examines the effects of the pandemic, especially students losing respect for teachers. Keywords: Behavior Management and Discipline, SWOT, Teaching and Learning.